Prospective study of hepatitis B virus reactivation in patients with hematological malignancies - Maurizio Pompili; Maria Basso; Stefan Hohaus; Giulia Bosco; Lorenzo Nosotti; Mariella D’Andrea; Susanna Fenu; Antonio Grieco; Luca Laurenti; Concetta Mirisola; Livio Pagano; Gian Ludovico Rapaccini; et al. (Annals of Hepatology, 2015)
Background and aim. The best strategy for managing patients with resolved hepatitis B virus infection (HBsAg negative, anti-HBc antibodies positive with or without anti-HBs antibodies) and hematological malignancies under immunosuppressive therapies has not been defined. The aim of this study was to prospectively analyze the risk of hepatitis B virus reactivation in these patients.Material and methods. Twenty-three patients (20 positive for anti-HBs) were enrolled. Eleven patients underwent hematopoietic stem cell transplantation (autologous in 7 cases, allogeneic in 4 cases) while the remaining 12 were treated with immunosuppressive regimens (including rituximab in 9 cases).Results. During the study no patient presented acute hepatitis. However, three anti-HBc/anti-HBs positive patients who were treated with allogeneic hematopoietic stem cell transplantation demonstrated hepatitis B virus reactivation within 12 months from transplant. No one of the remaining patients showed hepatitis B virus reverse seroconversion.Conclusions. Allogeneic hematopoietic stem cell transplantation is a high risk condition for late hepatitis B virus reactivation in patients with resolved infection. Reverse seroconversion seems to be a rare event in anti-HBc/anti-HBs positive patients submitted to autologous hematopoietic stem cell transplantation or systemic chemotherapy with or without rituximab.